2012
DOI: 10.1093/infdis/jis767
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Enhances the Potency of Posaconazole Against Rhizopus oryzae In Vitro and in an Experimental Model of Mucormycosis

Abstract: Combination posaconazole-tacrolimus therapy displays synergism in vitro and improved antifungal efficacy in vivo in 2 phylogenetically distinct models of mucormycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…The calcineurin inhibitors FK506 and cyclosporine A synergistically inhibit the growth of Mucorales in combination with other antifungal drugs (Dannaoui et al 2009;Narreddy et al 2010;Thakur and Revankar 2011). Efficacious outcomes were observed for combination therapy with posaconazole and FK506 in both Drosophila and murine cutaneous mucormycosis model systems (Lewis et al 2013). Another study found that FK506 treatment enforces M. circinelloides to grow as its less virulent yeast form, rather than its invasive hyphal form (Lee et al 2013).…”
Section: Iron Chelation Therapy and Other Novel Approachesmentioning
confidence: 99%
“…The calcineurin inhibitors FK506 and cyclosporine A synergistically inhibit the growth of Mucorales in combination with other antifungal drugs (Dannaoui et al 2009;Narreddy et al 2010;Thakur and Revankar 2011). Efficacious outcomes were observed for combination therapy with posaconazole and FK506 in both Drosophila and murine cutaneous mucormycosis model systems (Lewis et al 2013). Another study found that FK506 treatment enforces M. circinelloides to grow as its less virulent yeast form, rather than its invasive hyphal form (Lee et al 2013).…”
Section: Iron Chelation Therapy and Other Novel Approachesmentioning
confidence: 99%
“…This may have been because of the fact that posaconazole showsmodestactivityagainst R.oryzae, the most common species of mucormycosis (Dannaoui et al 2003;Barchiesi et al 2007;Rodriguez et al 2008;Ibrahim et al 2009). However, escalation of posaconazole exposure has shown efficacy, and combination with tacrolimus also showed enhanced effect (Rodriguez et al 2010;Lewis et al 2013). Continued PD study and analyses are important for future investigation to close knowledge gaps related to therapy for mucormycosis and other emerging fungal pathogens.…”
Section: Pk/pd Analysis Of Combination Therapymentioning
confidence: 99%
“…and the Mucorales (12)(13)(14). Our group recently reported that the combination of TCR with PCZ improves control of invasive, necrotizing cutaneous mucormycosis in immunosuppressed mice compared to that achieved with PCZ monotherapy (15). Since calcineurininhibiting agents have been extensively used in humans, it may be possible to manipulate this pathway, in order to develop novel strategies for recalcitrant fungal infections, such as mucormycosis.…”
mentioning
confidence: 99%